Conditions of candidacy for the House of Representatives under the Constitution of the Republic of Iraq for 2005: An analytical study - ثوني, علي عبيد; طالب, مصدق عادل (Journal of Legal Sciences, 2021)
The electoral process is of great importance in the political system that takes parliamentary democracy and represents the main stream of democratic practice. The degree of urbanization and progress of peoples is measured by the criterion of practicing democracy. This practice is justified by the citizens' awareness and awareness of their political rights،  Election.The right of candidacy is a real embodiment of the democratic dimension in allowing citizens to participate effectively In the administration of their country's affairs through parliamentary representation,  as well as activating citizens' exercise of their right to elect their representatives in the House of Representatives.We have dealt with the statement of conditions required by the Constitution and the law in the candidate, we have divided into two sections, we devoted the first to clarify the general conditions for the right of nomination for membership of the Iraqi Council of Representatives, while we devoted the second section of the special conditions for the right to nomination for membership of the Iraqi Council of Representatives, The Constitution of the Republic of Iraq 2005 and subsequent laws, and we concluded with a number of conclusions and recommendations.